CAPITAL BUDGETING ANALYSIS TO ASSESS THE FEASIBILITY OF INVESTMENT IN STATE-OWNED IDLE ASSETS - Ardhi, Dipta; Hidayatuloh, Rohmat (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
The purpose of this study is to determine and assess the feasibility of investment plans on idle state-owned assets in the context of optimizing assets using the capital budgeting method so that it can be known whether or not it is feasible to implement. This study uses a descriptive type of research with a case study approach. Research conducted on the assets of Ruko Kalimalang shows that by using the capital budgeting method, it can be seen that the investment plan is feasible to implement using the most optimal scheme, namely as is. The results of calculations using the payback period method show that the time required to return the investment is 2.66 years, less than the economic life of the asset, which is 15 years. The result of the calculation using the net present value (NPV) method is Rp. 131.137.929, -. This result is considered favorable because the NPV is positive (NPV> 0). The method of internal rate of return (IRR) is feasible to implement with the results of the IRR calculation being greater than the discount rate, namely 37.25% > 10%. Meanwhile, the profitability index is 2.86 > 1.